(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Bacteria multidrug-resistance (MDR) pathogens led to increasing hospital and community – acquired infections, for which current antibiotic therapies are not effective which represent a growing problem, its well-known that the silver ion and silver nanoparticles have strong effect against microbial. In this study we prepare silver Np in chemical reduction methods and tested it on two type of multidrug resistance bacteria :E-coli and S.aureus. The result showed that the sliver Np has a strong effect against gram-positive and gram-negative bacteria